The Role of the KL-YES Program as a Catalyst for Intercultural Dialogue in Promoting Tolerance - Widiyanti, Amelia; Eryantini, Intan (Paedagogie, 2026)
Amid globalization and cultural polarization, the Kennedy-Lugar Youth Exchange and Study (KL-YES) program emerges as a vital tool for fostering intercultural dialogue and tolerance among Indonesian youth in the US. This study aims to analyze KL-YES's role in intercultural dialogue, identify adaptation factors for Indonesian participants, and explore challenges with coping strategies. Employing a qualitative approach with phenomenology and narrative inquiry designs, the research targeted the 2025-2026 KL-YES cohort population, using purposive sampling for four key informants in New York, Colorado, Alaska, and Rochester. Data were gathered via in-depth semi-structured interviews, participant observations, and documentation, analyzed through thematic analysis with manual iterative coding. Results reveal KL-YES facilitates transformative dialogue in host families and schools, dismantling stereotypes via peer social capital, shared resilience, and religious identity visibility, despite pragmatic language barriers and cultural dissonance overcome by radical transparency. In conclusion, KL-YES builds global resilience and grassroots diplomacy, validating Intergroup Contact Theory and DMIS, with recommendations for reflective pre-departure training.